The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/puar.13734
|View full text |Cite
|
Sign up to set email alerts
|

Telework in public organizations: A systematic review and research agenda

Valentina Mele,
Paolo Belardinelli,
Nicola Bellé

Abstract: After a relatively slow policy and scholarly take‐up, recent developments created the urgency for massive efforts to implement and regulate telework in public organizations. We contribute to this debate through a systematic review of 120 studies across disciplines. Findings from our analysis reveal a few established antecedents of telework, including individual characteristics like family responsibilities and expected productivity, but also organizational aspects like supportive leadership, and contextual feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Pre‐pandemic literature focuses on individual and organizational benefits, such as job satisfaction, organizational commitment, job performance, turnover, professional isolation, relationship quality with supervisors and colleagues and cost reduction (e.g., Caillier, 2012, 2013; De Vries et al, 2019; Lee and Kim, 2018). In a recent review on telework in public organizations, Mele et al (2023) have shown that telework is associated with a decrease in turnover intention and higher job satisfaction, but also consistently appears to be a predictor of professional isolation, indicating that the impact of teleworking might differ based on individual and organizational characteristics.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Pre‐pandemic literature focuses on individual and organizational benefits, such as job satisfaction, organizational commitment, job performance, turnover, professional isolation, relationship quality with supervisors and colleagues and cost reduction (e.g., Caillier, 2012, 2013; De Vries et al, 2019; Lee and Kim, 2018). In a recent review on telework in public organizations, Mele et al (2023) have shown that telework is associated with a decrease in turnover intention and higher job satisfaction, but also consistently appears to be a predictor of professional isolation, indicating that the impact of teleworking might differ based on individual and organizational characteristics.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…They then provide a research agenda that extends the predominant focus on attraction by bridging public administration concepts with generic recruitment and selection research, to advance research on public sector hiring. Next, a systematic review by Mele et al (2023) considers telework in public organizations – a topic that received heightened urgency in the throes of the pandemic. They explored the topic by reviewing 120 studies across disciplines to reveal a few established antecedents of telework, including individual characteristics like family responsibilities and expected productivity, but also organizational aspects like supportive leadership, and contextual features like natural disasters.…”
Section: Articles Included In the Special Issuementioning
confidence: 99%